2022
DOI: 10.3390/su14148780
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Social Influence, Financial Literacy, and Saving Behaviour among Saudi Youth and the Moderating Effect of Self-Control

Abstract: This study examined the impact of social influence, i.e., parents and peers, on the level of financial literacy among Saudi young adults (students). It also assessed the effect of financial literacy on the development of saving behaviour and the role of self-control as a moderator in the relationship between financial literacy and saving behaviour among the same respondents. The study’s sample included 270 respondents (male and female) from an applied college affiliated with King Faisal University. The study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 49 publications
3
14
0
1
Order By: Relevance
“…In addition to FL, age, education, wealth and employment status are positively associated with saving behaviour, while household size is negatively associated with it (Baidoo et al, 2018). Alshebami and Aldhyani (2022) observed that financial socialization positively mediates the relationship between FL and savings behaviour. On the other hand, FL is also observed to positively moderate the relationship between risk preference and savings behaviour, and income is also noticed to significantly affect saving behaviour through such risk preference (Amari et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…In addition to FL, age, education, wealth and employment status are positively associated with saving behaviour, while household size is negatively associated with it (Baidoo et al, 2018). Alshebami and Aldhyani (2022) observed that financial socialization positively mediates the relationship between FL and savings behaviour. On the other hand, FL is also observed to positively moderate the relationship between risk preference and savings behaviour, and income is also noticed to significantly affect saving behaviour through such risk preference (Amari et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 90%
“…, 2018). Alshebami and Aldhyani (2022) observed that financial socialization positively mediates the relationship between FL and savings behaviour. On the other hand, FL is also observed to positively moderate the relationship between risk preference and savings behaviour, and income is also noticed to significantly affect saving behaviour through such risk preference (Amari et al.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Due to its distributed nature, blockchain technology may exacerbate the existing digital divide between the well-off and the rest of the population (Henninger & Mashatan, 2022). The gap between the financially literate and the financially illiterate, the wealthy and the poor, may grow even wider as a result of this (Alshebami & Aldhyani, 2022) tax evasion, and fraudulent transactions may all be made easier by the anonymity and lack of oversight in some blockchain systems (Teisserenc & Sepasgozar, 2021b). The money from crimes and bribes can be concealed by the anonymity of online transactions (Sanz-Bas et al, 2021).…”
Section: Environmental Impactmentioning
confidence: 99%
“…According to Aguila et al (2011), retirees tend to control their spending and practice responsible financial behaviour due to changes in lifestyle and better money management. Moreover, individuals who practice responsible financial behaviour, especially in financial planning and regular savings, have higher financial stability and better living standards (Alshebami & Aldhyani, 2022; Sabri & Aw, 2020; Topa et al, 2018; Xiao, 2008). In addition, a review of past studies reveals that financial behaviour plays an essential role in retirement preparedness (Hauff et al, 2020; Noviarini et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%